2016
DOI: 10.4037/aacnacc2016667
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support as a Novel Strategy to Mitigate Post–Intensive Care Syndrome

Abstract: Post-intensive care syndrome, a condition defined by new or worsening impairment in cognition, mental health, and physical function after critical illness, has emerged in the past decade as a common and life-altering consequence of critical illness. New strategies are urgently needed to mitigate the risk of neuropsychological and functional impairment common after critical illness and to prepare and support survivors on their road toward recovery. The present state of critical care survivorship is described, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 59 publications
1
61
0
6
Order By: Relevance
“…A model integrating early, time-limited post-ICU follow-up (including nurses, physicians, physical therapists, pharmacists, social workers, and peer support) is also being disseminated across Scotland [179]. In the United States, there is growing interest in both post-ICU clinics and post-ICU peer support models [180]. A growing number of United States hospitals report focusing on sepsis as part of the Centers of Medicare and Medicaid Services (CMS) program Partnership for Patients that aims to a 12% reduction in 30-day readmissions [181].…”
Section: Are There Potential Post-discharge Interventions That Can Immentioning
confidence: 99%
“…A model integrating early, time-limited post-ICU follow-up (including nurses, physicians, physical therapists, pharmacists, social workers, and peer support) is also being disseminated across Scotland [179]. In the United States, there is growing interest in both post-ICU clinics and post-ICU peer support models [180]. A growing number of United States hospitals report focusing on sepsis as part of the Centers of Medicare and Medicaid Services (CMS) program Partnership for Patients that aims to a 12% reduction in 30-day readmissions [181].…”
Section: Are There Potential Post-discharge Interventions That Can Immentioning
confidence: 99%
“…To augment existing support networks, peer support is another potentially valuable intervention (57,58) that could complement a redesign of multidisciplinary follow-up care that aims to better support survivors and their family and caregivers. Consistent with the qualitative experience of survivors of acute respiratory distress syndrome and sepsis (18,19,59), clinicians have a profound therapeutic impact on survivors during recovery in terms of their ability to reassure, educate, rehabilitate, prepare, and support survivors for life after critical illness.…”
Section: Original Researchmentioning
confidence: 99%
“…This study suggests a similar wide‐reaching effect of social support, helping with feelings of anxiety and low mood, facilitating attendance at hospital appointments and providing informal care services, in a more ‘social assistive’ role, as discussed by Iwashyna and Netzer (). The significance of peer support was another key finding in this study, as shown in other studies (McPeake and Quasim, ; Mikkelsen et al ., ).…”
Section: Discussionmentioning
confidence: 97%